Infecção do trato urinário associada ao uso do cateter vesical em paciente crítico: impacto do bundle na prevenção - Écila Campos Mota (2019)
Urinary tract infection is one of the most common health care problems, especially in the intensive care unit (ICU), and is mostly associated with the use of bladder catheter (ITU-AC), significantly impacting mortality, morbidity and cost of treatment. This study aims to analyze the impact of bundle implantation on ITU-AC prevention in critically ill patients, as well as to evaluate the skills of professionals who insert and manipulate the bladder catheter (BC) in relation to prevention measures of this infection. This is an epidemiological intervention study conducted in the ICU for adult patients in a highly complex philanthropic hospital in the state of Minas Gerais. The study stages comprised three moments: pre-intervention, intervention and post-intervention. In the pre-intervention, or baseline period, the incidence density of ITU-AC from July 2016 to June 2017 was determined by analyzing the medical records. It was complemented by an approach to the professionals involved in the insertion or manipulation of the CV, through interviews to assess knowledge and direct observation to adhere to the ITU-AC best practices for prevention. In the intervention, the bundle was implemented in the unit and professionals were invited to attend a training/review/update session on ITU-AC prevention measures in which active methodologies were adopted, with practical demonstrations, playful interventions and procedure simulation (animation video). After the intervention, 30 days after the intervention, the occurrence of UTI-AC was monitored and a second assessment of the knowledge and adherence of professionals to the UTI-AC prevention measures was conducted. Descriptive analyzes were performed and in the comparison of the two periods (pre and post intervention), for categorical variables Pearson's Chi-squared test or Fisher's exact test were performed and numerical variables were used the non-parametric Mann-Whitney test. To test normality, the Kolmogorov-Smirnov test was used. The significance level for statistical inference was 0.05 with a 95% confidence interval. This study was approved by the Research Ethics Committee of the Universidade Federal de Minas Gerais, under opinion 2.069.140 and CAAE: 66149217.3.0000.5149. In the pre-intervention, the BC was used in 402 (93.3%) patients, with a predominance in males (56.7%). The ITU-AC incidence density was 4.8 per 1,000 catheter/day, most (80.6%) with no indication for catheter use and 86.7% had no prescription for insertion and/or maintenance. The average time between BC insertion and diagnosis of infection was 11.3±6.3 days (6 to 28 days). The statistically significant factors (p<0.005) related to UTI-AC were length of stay in the unit (16.7±9 days), length of stay of the BC (12.7±6.9 days) and use of antimicrobials during intensive care unit admission (8.6±6.3 days). In the evaluation of the adherence of professionals to the prevention measures of UTI-AC, 451 observations were made related to the maintenance of the BC focusing on its fixation, maintenance of the collecting bag, and volume and urinary flow of the drainage system. As nonconformities, inadequate fixation and drainage bag were verified with more than three quarters of its filled capacity (97.7% and 3.5%, respectively). Regarding the manipulation of 556 BC, non-compliance with urethral meatus hygiene occurred in 22.9% of the situations, and non-adherence to hand hygiene before and after BC handling was 94.2% and 66.5%, respectively (p=0.002). In the self-reported knowledge of the multiprofessional team, 32 professionals were part of the study, 20 nursing technicians, eight doctors and four nurses. The median percentage of self-reported knowledge on indications for BC insertion was 16.7% and the insertion technique was 50%. The professionals with the highest median accuracy in the indications were doctors (16.6%) and in the insertion technique, nursing technicians (50%). Regarding prevention measures for UTI-AC, the median knowledge was 23.1% and the professionals with the most knowledge were nurses and doctors with 30.8%. During the intervention, 23 (96%) nursing technicians, four (100%) nurses and four (30%) doctors participated in the training sessions in the various shifts (morning, afternoon and evening). Post-intervention, BC was used by 94.3% of patients, increasing incidence density to 7.39 per 1,000 BC/day. There was a significant improvement in the decrease in the length of stay of the BC and in the percentage of antimicrobial use. For adequate indication of BC insertion, the difference between the two periods was not significant (p = 0.06). The factors that were significantly associated with UTI-AC were the same as those of the pre-intervention: length of stay in ICU and hospital, length of stay of BC and days of antimicrobial use in ICU (p<0.05). The adherence of professionals to the ITU-AC prevention measures showed improvement in all indicators, reaching adequacy rates of 100% or close to this value in maintaining the BC. Regarding manipulation, despite the increase in adherence in all preventive measures of UTI-AC after the intervention, regarding hand hygiene, this indicator remained below 50%. In the self-reported knowledge of the multiprofessional team, there was a tendency to increase in all preventive measures of UTI-AC. Significant differences (p<0.05) were found in the description of the moments for hand hygiene, indications for insertion of the BC, measurement of adherence to the barrier measurement in the insertion technique, and prevention measures of ITU-AC during manipulation and BC maintenance. The impact of the ITU-AC prevention bundle achieved positive results. However, in some actions, such as: registration of the appropriate indications for the use of BC, knowledge about the prevention measures of ITU-AC and poor adherence to hand hygiene during manipulation and maintenance of VC, it is found that efforts and feedback are needed from professionals, clearly showing that bundle can be an effective strategy, as long as its follow-up is sustained and long-term to incorporate knowledge into the practice of professionals and not just a punctual intervention. Nevertheless, its implementation in clinical practice, in this research, served to identify gaps that require change and usually involve education, commitment and implementation of institutional protocols. Professionals need to know and execute all measures properly, as knowledge in isolated measures is not sufficient to ensure excellence in the care provided.